A Review of 3D Digital Garment Simulation Strategies for Enhanced Wearables and Medical-Grade Applications (Journal of Fiber Bioengineering and Informatics, 2024)
This paper thoroughly reviews the current state of digital simulation technology and its strategicimplementation across applications, primarily focusing on advanced compression garments. Despite thesignificant impact of three-dimensional digital garment simulators (3DGS) on the apparel and textileindustry, their usage has largely been confined to visual prototyping, visual quality check, or marketingtools. Notably, these simulators’ physical or mechanical representation has been understated in thecontext of advanced functional manufacturing. This review delves into the potential strategic integrationof virtual physical properties to augment garment functionalities, particularly within wearables andmedical-grade compression fields. The initial phase of this study provides a comprehensive overviewof the status of 3D garment simulation tools and their digitisation capabilities. Subsequently, a gapanalysis focuses on minimising disparities between simulated and actual physical property assessments.Despite the absence of reliability and standardised testing within a virtual environment, this paperfocuses on the relevant literature to gain crucial insights for apparel and textile engineers, providinga nuanced understanding of the capabilities and limitations of 3DGS mechanical representation inenhancing advanced functionalities, specifically customised for diverse end-users.
Keywords: 3D Digital garment simulator; Advanced compression garment; Digital strategy; Medical-grade compression; Simulated physical property; Virtual evaluation